Minimalonomics: A novel economic model to address environmental sustainability and earth's carrying capacity. (15th October 2022) - Sarkar, Atanu
Abstract: Mass production and insatiable consumption are leading to enormous waste worldwide, contaminating the entire biosphere, losing biodiversity, and climate change. Craving for materialistic things and buying sprees for newer products indicate the dominant roles of human behavior in imminent ecological, social, and economic crises. However, existing global environmental governance has failed to address the current consumption patterns, particularly in rich countries. There is no inclusive developmental policy that integrates human behavior intervention to reduce unnecessary consumption, closed-loop material flow systems to keep waste out of the system, and economic strategies addressing ecological disaster from a social equity standpoint. The paper is based on a critical literature review of three concepts, relevance of behavioral economics in pro-environmental decision making, scope and limitations of circular economy as technological solutions, and conflicts of ecological economics with dominant neoclassical economics pitting 'degrowth' as an alternative. The paper proposes a theoretical concept of a novel economic model ( minimalonomics ) that aims to provide an institutional framework for a minimalist lifestyle without compromising wellbeing, prosperity, equity, and justice. The model focuses on minimizing consumption at the individual and societal levels, integrating theories and principles of ecological economics and behavioral economics, and efficient application of circular economy. Minimalonomics emphasizes creating a pro-environmental attitude in all levels of society (producers, consumers, and government) and translating the individual's perspective to collective and coordinated action for protecting the biosphere. Contrary to the standard economic approach, minimalonomics restores the value of localization and appropriates local social and cultural norms regarding consumption, waste reduction, and environmental protection; thus, the model is more inclusive. Minimalonomics is a novel concept; therefore, before application to governance and policies, it needs further research on creating theories, developing indicators, and testing them in the field. Highlights: Craving for new things & endless consumption generating enormous amount of wastes. Waste mitigation strategies fail to address the current patterns of consumption. Promote minimalist lifestyle at individual levels, and degrowth at policy levels. Minimalonomics emphases on creating a pro-environmental attitude in the society. Need to integrate ecological economics, behavioral economics and circular economy.